Determinants of Investors' Awareness of Online Trading in the Nepal Stock Market: An Empirical Assessment Using Binary Logit Model (Quest Journal of Management and Social Sciences, 2023)
Background: Online trading is becoming a prominent method of conducting stock exchanges through web platforms. While many regions worldwide have embraced online trading, its introduction in Nepal is relatively recent. The Nepalese stock market is considerably smaller than its neighboring nations, highlighting the significance of capital in a country's economic progress.Objective: The main objective of this paper is to investigate the factors that influence investor awareness of online trading within the Nepal Stock Exchange. The study focuses on investors who engage in stock market activities online, examining the variables of better online trading (dependent variable), facility in online trading, and investors' intention to invest (independent variables) in the context of online trading in Nepal.Methods: To achieve this objective, the study employed a non-probability convenience sampling technique, selecting 403 samples from the population of online investors. The research process incorporated three key instruments: expert opinions, structured questionnaires for surveys, and observational data collection.Results: The study's findings reveal that the majority of investors (83.4%) in Nepal possess a comprehensive awareness of online trading. Notably, the primary source of this awareness is brokers, accounting for 58% of investor knowledge dissemination.Conclusion: This research underscores the growing awareness of online trading within the Nepal stock exchange. Although Nepal's stock market is relatively diminutive compared to neighbouring nations, brokers play a vital role in educating investors about online trading. As investor interest in online trading rises, stakeholders and regulators must adapt to this evolving financial landscape.Implications: Understanding the factors that drive awareness and participation in online trading is critical for the development and growth of the financial sector in Nepal. Stakeholders must enhance educational efforts and facilitate investor-friendly policies further to bolster the online trading ecosystem in the country.Keywords: Online trading, Stock market, NEPSE, SEBON, NepalJEL Classification: G24; G32